Pengaruh Likuiditas, Profitabilitas, Dan Good Corporate Governance (GCG) Terhadap Return Saham - Abdul Wahab Yunus; Idrus Usu; Hasanuddin Hasanuddin; Deby R Karundeng (JSAP: Journal Syariah and Accounting Public, 2025)
This study aims to determine the effect of liquidity, profitability, and Good Corporate Governance (GCG) on stock returns in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The data collection technique uses secondary data, with a population of 30 companies and a sample of 16 companies selected through purposive sampling techniques. The analytical tool used is multiple linear regression analysis. The results of the study indicate that: (1) Partially, liquidity (CR) has a positive and significant effect on stock returns; (2) Partially, profitability (ROE) has no significant effect on stock returns; (3) Partially, Good Corporate Governance proxied by Independent Commissioners (IC) has no significant effect on stock returns; (4) Simultaneously, liquidity, profitability, and Good Corporate Governance have a significant effect on the stock returns of food and beverage sub-sector companies listed on the IDX during the 2019–2023 period.